A Retrospective Observational Study Examining the Effect of Thoracic Epidural and Patient Controlled Analgesia on Short-term Outcomes in Blunt Thoracic Trauma Injuries. Issue 2 (January 2016) - Baker, Edward James; Lee, Geraldine Ann
Abstract : Abstract: Effective analgesia in the early stages after any major traumatic event remains pivotal to optimal trauma management. For patients with significant thoracic injuries, this is paramount to ensure ongoing efficient respiratory function. The aim of this study was to investigate the use of analgesic modes in the management of patients with a primary thoracic injury and blunt mechanism of injury. By understanding variables that influence the use of varying analgesic modes and influence the development of pulmonary complications, there should be more uniform evidence-based prescription in the future. This retrospective study considered analgesic use in patients admitted after blunt thoracic injuries at one major trauma center over a 2-year period. Pulmonary complications measured included both infective and ventilator-associated failure. Univariate and multivariate analyses were used to identify patient and injury severity characteristics and their association with respiratory complications. A total of 401 cases were reviewed and analyzed: 159 received Patient Controlled Analgesia (PCA), 32 received PCA and epidural analgesia (EA), 6 received EA alone, and 204 received interval-administered analgesia. There were no significant differences in the rates of complication when compared between analgesic modes. Patients who developed pneumonia had significantly increased number of thoracic fractures and underlying organ injury ( P  < 0.05). Logistic regression analysis highlighted duration of intercostal drain insertion (OR 1.377, P  = 0.001) and premorbid cardiac disease (OR 2.624, P  = 0.042) and ICU length of stay (OR: 1.146, P  < 0.001) as significant predictors of developing pneumonia in this patient group. Examining the different analgesic modes, this study failed to identify a particular analgesic mode that was more effective in preventing pulmonary complications in blunt thoracic injuries. However, variables that may influence usage of different analgesic modes and high-risk groups for the development of pneumonia were identified. Further work is warranted to consider the long-term benefits of analgesia in patients post-blunt thoracic injuries.